Hands-on training on reduction of setup times (SMED) - Sousa, Rui M. (2018)
Besides high quality, fast delivery and low price, the current markets demand high product diversity. The mass customization concept confirms this tendency in many types of industries and implies serious challenges to the companies. Thus, the ability to quickly change the type of product being produced (setup process) is a crucial requisite for the companies’ competitiveness, and eventually for their survival. Inherent to the Lean Manufacturing paradigm, the Single Minute Exchange of Die (SMED) methodology was specifically developed to reduce the setup time (equipment, workstation, assembly line, etc.), by carrying out a series of stages and using a set of tools/techniques. The objective of this hands-on training session is to teach trainees how to apply SMED in industry. The session includes a brief introduction to the fundamentals of SMED, followed by the hands-on session itself where the trainees will use the so-called SMED kit (physical components), through three runs, to achieve a good solution in terms of setup time. In fact, this session uses a serious game (involves competition), which is a recognised approach to achieve high levels of trainees’ engagement and knowledge acquisition/retention. This hands-on session clearly illustrates the application of the SMED methodology, especially in terms of applicable techniques/tools, and can be used both in industry and academia.